SURVEI DAN ANALISIS PENGGUNAAN INTERNET DI UNIVERSITAS JANABADRA - Ryan Ari Setyawan; Taofiq Krisdiyanto (Universitas Janabadra, 2020)
This research was conducted with the aim to find out the largest absorption of bandwidth used to access anything (eg social media, youtube and others) and to find out the factors that make internet connections at Janabadra University often not connected or slow connections. The method used in this study is to use the method of distributing questionnaires to all internet users at Janabadra University both employees, lecturers and students then the results of the questionnaire are processed and analyzed using regression analysis. Meanwhile, to determine the amount of bandwidth traffic using Quality of Service (QoS) analysis namely throughput, jitter and delay. To measure the QoS, the software is wireshark. Wireshark is used to record or view internet access distribution traffic that is used by users in Janabadra University. The results obtained that the highest bandwidth uptake is used for access to YouTube, online games and social media live streaming and it is evident from the analysis of internet usage traffic at Janabadra University that due to bandwidth is often used for unsuitable access, it produces a very small throughput with an average 2,092 kbps average. Keywords : Delay, Jitter, Throughput, Quality of Service.